Geopsychology of instrumental aggression: daily concurrence of global terrorism and solar-geomagnetic activity (1970-2018) - Mulligan, Bryce; Koren, Stanley (Advances in Social Sciences Research Journal, 2021)
Formal scientific study of the geopsychology of human aggression dates back at least a century and has consistently demonstrated a positive association between solar-geomagnetic activity and aggressive behaviour. Advances in the theories, methodologies, and practical applications of geopsychology could therefore contribute to collective efforts to comprehend, to forecast, and to develop interventions for aggressive behaviours such as those seen in terrorism. This requires a rigorous and precise estimate of the magnitude of association between solar-geomagnetic activity and aggression using a representative, contemporary sample of strictly-operationalized behaviour. Here we show that days in recent history (1970-2018) with the lowest levels of instrumental human aggression (number of casualty-associated terrorism incidents) also had the lowest levels of solar and geomagnetic activity, and that stepwise increases in human aggression were mirrored by progressive increases in solar activity. We used Bayesian methods robust to outliers and heterogeneity of variance to analyze the most comprehensive and contemporary global database of terrorism incidents available, which included more than 106,000 unique instances of instrumental aggression spanning 48 years. We conclude that there is a small, nonzero promotional effect of solar-geomagnetic activity on terrorism-related aggression. This may reflect the fact that solar-geomagnetic activity serves as a zeitgeber that coordinates the expression of instrumental aggression across an aggregation of susceptible individuals. We propose that many behaviours – even instrumental acts such as terrorism which are presumed to involve a degree of planning and intention – may be subject to subtle geopsychological induction or suppression.